New applications of duodenotomy via Narciso Hernández - Praderi, Raúl; Navarro, Teodoro; Cardoso, Tabaré; Abascal, Winston; Beguiristain, Alberto (Cirugía del Uruguay, 1986)
Description of three new indicatíons of the approach to the second duodenal knee through the transmesocolic vla propounded by N. Hernández. The first one was proposed by Dr. Carlos Pera Madrazo, of Cordoba (Argentina), to make an hepato-jejunostomy connecting same to the duodenum, using in case of benign is the intraduodenal inspection of the first section; it was used to remove an oblitum. The third one is the inframesocholic transduodenal approach to old choledocoduodenostomies to calibrate by means of transhepatic tubes neoplasic stenosis caused by tumors or ganglia.